Spatial variation and metabolic diversity of microbial communities in the surface sediments of the Mariana Trench - Wang, Fangzhou; Zhang, Yue; Jing, Hongmei; Liu, Hao (Frontiers in Microbiology, 2022)
Mariana Trench represents the deepest and one of least explored biosphere on Earth, and its carbon sources including euphotic sinking, lateral transportation and diffusion from underlying crust, etc. By far the spatial variation of microbial community with associated organic carbon degradation potential in the surface sediments of the Mariana Trench were still largely unknown. Based on the high-throughput 16S rRNA amplicon sequencing, significantly different microbial community structure was overserved between the shallow (< 10,000 m) and deep stations (> 10,000 m), which could be explained by spatial variation of α-Proteobacteria and Crenarchaeota, with sampling depth and TC content as the environmental driving forces. During the 109-day incubation with Biolog EcoPlate™ microplate, polymers and carbohydrates were preferentially used, followed by amino acids and carboxylic acids, and microbial metabolic diversity was significantly different between the shallow and deep stations. This could potentially be attributed the metabolic capabilities of different microbial groups with varied ecological niches, and reflected the initial preference of carbon source by the nature microbes as well. Our study obtained a rough assessment of physiological and taxonomic characteristics of the trench sediment microbial community with polyphasic approaches. In the future, isotopic tracing experiments together with meta-transcriptomics would help to elucidate the role of in situ microbial community involved in the process of complex organic matter mineralization occurred in the trenches.